Validation of Iron-Food Frequency Questionnaire for Assessing Iron Intake in Women of Reproductive Age: A Cross-Sectional Study on Female Undergraduate Students in Indonesia - Luftimas, Dimas Erlangga; Lucita, Ardya; Wiramihardja, Siska; Rusmil, Viramitha Kusnandi (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2021)
The aim of this study is to develop and assess the validity of the Iron-Food Frequency Questionnaire (Iron-FFQ) in assessing the iron intake of reproductive age women. This cross-sectional study involved randomly selected female undergraduate students at Jantinangor, Sumedang district, West Java (n=94) as respondents. The validity test compared the iron intake using Iron-FFQ with the 3-Days Food Diary (FD). The iron contents of each food from both methods were obtained from Indonesian Food Composition Table (2017). Iron contents were analyzed using the Wilcoxon signed rank test and Spearman’s rank correlation. The results showed significant correlation in iron content between Iron FFQ and the 3 Days FD with r=0.25 for the tubers, nuts, and vegetables group, and r=0.21 for milk and fish (p<0.05). While, statistically non-significant correlations were found for the rest of the food groups (cereal, meat, poultry, eggs, fruits, fats, sugar, syrup, confectionary, and spices) with r ranged from r=0.19 to r=0.01. The average assessment value using Iron-FFQ was lower than the 3-Days Food Diary, especially in the food and beverages group (-100%), sugar, syrup, and confectionary (-93.8%), and vegetables (-88.5%). In conclusion, Iron-FFQ can be declared valid for measuring iron intake from some food group such as starchy tubers, fish, shellfish and shrimp, nuts, vegetables, and milk as they have an acceptable correlation value.